(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Patients with right ventricular infarction is a critical condition and may cause adverse cardiac events. Objective: The purpose of the present study was to compare the in-hospital complications among patients with right ventricular infarction based on TIMI risk score. Methodology: This prospective observational study was conducted in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from May 2007 to April 2008 for a period of one year. All the patients who were admitted into the coronary care unit of NICVD with acute inferior myocardial infarction with or without anterior myocardial infarction were selected as study population. Inclusion Criteria were patients admitted in CCU (NICVD) with acute inferior myocardial infarction with right ventricular infarction. Patients were categorized into two groups according to the extent of TIMI risk score. Patients with low TIMI risk score (0 to 3) were included in Group I and patients with high TIMI risk-score (4 to 14) were include in group II. Patients were followed up in their hospital stay to see the incidence of major cardiac events. Results: A total number of 60 patients with right ventricular infarction of which 30 consecutive patients with low TIMI risk score (0 to 3) were in Group I and 30 consecutive patients with high TIMI risk score (4 to 14) were in Group II. In-hospital mortality was 18.3% in the study populations and it was significantly higher in group II (33.3%) than group (3.3%). The next most common complication is cardiogenic shock followed by complete heart block, Cardiac arrest, VT and 2nd degree heart block. Conclusion: In conclusion the in-hospital mortality in the study populations is significantly higher in group II than group I Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):143-146